Descentralizacion forestal en Bolivia: implicaciones en el gobierno de los recursos forestales y el bienestar de los grupos marginados - Pacheco, P. (CIFOR and IDRC, 2006)
This book presents the results of the Bolivian case study on forestry decentralization. It is part of a larger CIFOR study also undertaken in Brazil, Guatemala, Nicaragua and Honduras, which investigates forestry decentralization processes and, in particular their effects on forest-dependent groups. Since the 1990’s, Bolivia has played a leading role in Latin America with regard to the transfer of political, administrative and fiscal responsibilities and authority from national to municipal governments. Decentralization also included important aspects of forest management, which was particularly affected by new land policies. Among his conclusions, the author points out that, although municipal governments are now more active in poverty alleviation initiatives, their conception of local development still fails to consider the potential use of natural resources. At the same time, small rural producers and indigenous groups, who have recently been granted formal land rights, have not been given the decision-making authority to define the use of those resources. The first half of the book provides pertinent information on the Bolivian forest sector, presents the decentralization framework promoted by the government, and discusses the legal, institutional and informal arrangements of forest governance. The author then analyses power disputes among a variety of actors and institutions and examines the effects of decentralization on the wellbeing of various social groups. Finally, he proposes key topics for further research that would advance the forestry decentralization debate in Bolivia.